2013
DOI: 10.1016/j.jmb.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

β-Hairpin-Mediated Nucleation of Polyglutamine Amyloid Formation

Abstract: The conformational preferences of polyglutamine (polyQ) sequences are of major interest because of their central importance in the expanded CAG repeat diseases that include Huntington’s disease (HD). Here we explore the response of various biophysical parameters to the introduction of β-hairpin motifs within polyQ sequences. These motifs (trpzip, disulfide, D-Pro-Gly, Coulombic attraction, L-Pro-Gly) enhance formation rates and stabilities of amyloid fibrils with degrees of effectiveness well-correlated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
194
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(208 citation statements)
references
References 74 publications
(150 reference statements)
14
194
0
Order By: Relevance
“…S1 shows that these NMR signals are indistinguishable from those of "simple" polyQ fibrils without htt flanking domains (11,(15)(16)(17). Previous studies have noted that these chemical shifts are indicative of β-sheet rather than α-helical or random coil structure.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…S1 shows that these NMR signals are indistinguishable from those of "simple" polyQ fibrils without htt flanking domains (11,(15)(16)(17). Previous studies have noted that these chemical shifts are indicative of β-sheet rather than α-helical or random coil structure.…”
Section: Resultsmentioning
confidence: 85%
“…Although it is generally accepted that the mature fibrils feature antiparallel β-sheets, there continue to be conflicting models not only for their fibrillar structure, but also for the specifics of the multistage pathway by which they are formed. For instance, intramolecular polyQ-based β-hairpins are both proposed to be either nuclei that initiate the rapid formation of β-hairpinbased fibrils (11) or semistable monomeric or oligomeric species that at least transiently resist progression to fibrils (12). Concrete structural data on the fibril's internal structure are essential prerequisites for a truly molecular understanding of the way in which mutant htt exon1 and other polyQ disease proteins misfold and aggregate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Structural characterization of the aggregates (13,14,(18)(19)(20) has shown that, even when there are flanking sequences, polyQ remains the fiber core and adopts a β-hairpin conformation. In this paper, we use energy landscape analysis to provide a detailed molecular picture of the aggregation process of the peptide encoded by HTT exon 1, focusing on how the flanking sequences influence aggregation.…”
mentioning
confidence: 99%
“…The aggregation of the diseasecausing peptide is, however, further complicated by the presence of flanking amino acid sequences in fragments encoded by HTT exon 1. Experiments indicate that the addition of NT17 at the N terminus of polyQ enormously accelerates the aggregation, probably by encouraging the formation of prefibrillar oligomers (10)(11)(12)(13)(14)(15)(16), whereas the addition of the proline-rich region at the C terminus decreases the rate of aggregation apparently without changing fundamentally the mechanism (10,16,17). Structural characterization of the aggregates (13,14,(18)(19)(20) has shown that, even when there are flanking sequences, polyQ remains the fiber core and adopts a β-hairpin conformation. In this paper, we use energy landscape analysis to provide a detailed molecular picture of the aggregation process of the peptide encoded by HTT exon 1, focusing on how the flanking sequences influence aggregation.…”
mentioning
confidence: 99%